PENGARUH KONTRAK PSIKOLOGIS TERHADAP PERILAKU KERJA INOVATIF DENGAN WORK ENGAGEMENT SEBAGAI VARIABEL INTERVENING - Ukiningtyas, Ahimsa (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2016)
Abstract:This study explored the relationship effect between the types of psychological contract and innovative work behavior. It is focusedon the direct effect and indirect effect ofthe types of psychological contract and innovative work behavior mediated by work engagement. The subjectswere 81 employees from the low level management of Public Broadcasting Institutionschosen by using a proportionate random sampling technique. Data were collected using questionnaire and to avoid bias in measuring the dependent variables, data were sourced from the employees and also their superiors. This research used Structural Equation Mpdelling–Partial Least Squareas the analysis technique. The results show that: (a) relational contract does not affect innovative work behavior, (b) transactional contract does not affect innovative work behaviour, (c) relational contract affects work engagement, (d) transactional contract does not affect work engagement, (e) work engagement affects innovative work behaviour, (f) work engagement does not mediate the positive relationship between relational contract and innovativebehavior, and (g) work engagement does not mediate the negative relationship between transactional contracts and innovative behavior Keywords: Psychological Contract, Relational Contract, Transactional Contract, Innovative Work Behaviour, Work Engagement